Interferensi Bahasa Indonesia pada Pembelajaran Bahasa Jepang: Indonesian Interference to Japanese Language Learning - Made Henra Dwikarmawan Sudipa (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2020)
This article aims at discussing Japanese language as second language acquired by Indonesian students. There are difficulties at learning Japanese grammatical rules, including: sentence structures, phrases formulation, and using appropriate particles. The source of the data was from the test results of Mahasaraswati students who learns Japanese language. The data was collected by questioner method, in the form of test. The collected data was analyzed by interference approach, and error analysis. Interference approach manages to find and analyze the problems of learning Japanese language. The results showed that Indonesia language grammatical rules could affect in Japanese language.